Distribution of Radionuclides in Surface Soil and Bottom Sediment in the District of Jessore, Bangladesh and Evaluation of Radiation Hazard (Journal of Bangladesh Academy of Sciences, 2009)
This paper presents the first reports on the natural and anthropogenic radionuclides in soil and sediment of Jessore, a south-western district of Bangladesh. Surface soil and freshwater sediment were collected from in and around some major water-bodies of this district. To assess the radiological hazard of the natural radioactivity, the radium equivalent activity, the absorbed dose rate, and the external and internal hazard indices were calculated. In the soil and sediment in general, the activity concentration of 232Th was found to be higher than that of  226Ra, while that of 40K markedly exceeds the values of both 226Ra and 232Th. The average activities of 226Ra and 232Th in this area were found to be higher than the world average. There was no activity due to fallout (137Cs) in this area. The radium equivalent activity and the absorbed dose rate due to the natural radionuclides were found to be respectively lower and higher than the world average. The external and internal hazard indices were found to be well below the hazard limit of unity. Our results compare fairly well with other published results.  Key words: Soil, Sediment, Natural lake, Radioactivity, Dose rate DOI: 10.3329/jbas.v33i1.2956 Journal of Bangladesh Academy of Sciences, Vol. 33, No. 1, 117-130, 2009